From Pulpit to Social Media: Reinterpretation of Education in the Perspective of K.H. Ahmad Dahlan in the Digital-Influencer Era - Suripto; Aziz, Muhajir Sulthonul (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This research aims to reinterpret the role of educators from the perspective of K.H. Ahmad Dahlan amid the phenomenon of educational influencers on social media TikTok. The development of the digital space has presented new educational figures that greatly influence students’ motivation and character, mainly Generation Z. The research uses a qualitative approach with critical discourse analysis in this context. It uses Surah Al-Ma’un and Al-'Ashr as normative frameworks in analyzing Islam’s educational values and social practices in digital content. The data was collected through observations, TikTok content documentation, and in-depth interviews with six students and two teachers at two secondary schools in Tulungagung Regency. The study results show that educational influencers have played a role as non-formal educational agents with the power of symbolic capital that students widely accept. As many as 68% of students actively follow educational content on TikTok, and 60% say it is easier to understand the messages conveyed by influencers than teachers in the classroom. Within the framework of Bourdieu and Counts’ theory, these findings show a shift in educational authority and the emergence of new learning habits based on relationships and personal experiences. From the perspective of K.H. Ahmad Dahlan, this phenomenon can be seen as a new form of digital charity practice that, if directed by Islamic values, has the potential to strengthen the transformation of education that is grounded and adaptive in the digital era.